Klasifikasi Teks Bahasa Indonesia Pada Dokumen Pengaduan SAMBAT Online Menggunakan Metode Naive Bayes dan Kombinasi Seleksi Fitur - Hilmy Khairi Idris; Mochammad Ali Fauzi; Indriati Indriati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
SAMBAT Online is a form of e-Government realization in Malang City. SAMBAT Online or The Integrated Online Community Application System is a platform of a website provided by the Malang City Government to receive complaints, criticisms, suggestions, or questions to the government. Each incoming report will be grouped manually by the SAMBAT Online system manager. Grouping is based on The Regional Work Unit (SKPD) which is handled manually. Therefore, a classification system was built to save time in the process of grouping reports to SKPD using the Naive Bayes method and the Combination of Feature Selection between Chi-Square and Information Gain. In the tests conducted, the system succeeded in providing better accuracy results when using feature selection than without using feature selection with an accuracy value of 83.33%. Furthermore, when a feature selection combination is performed, the results of the accuracy obtained are the same as the results without a combination of 83.33%. So, the combination of selection has not been able to provide better results.